2012
DOI: 10.1007/s00170-012-4152-x
|View full text |Cite
|
Sign up to set email alerts
|

Cutting torque and tangential cutting force coefficient identification from spindle motor current

Abstract: This article presents an enhanced methodology for cutting torque prediction from the spindle motor current, readily available in modern machine tool controllers. This methodology includes the development of the spindle power model which takes into account all mechanical and electrical power losses in a spindle motor for high-speed milling. The predicted cutting torque is further used to identify tangential cutting force coefficients in order to predict accurately the cutting forces and chatter-free regions for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…That is, the surface profile error can be directly determined by the applied feed rate and axial cut depth during milling operation. By curve fitting on the realistic experiments undertaken beforehand, the current applied to spindle motor with respect to rotational spindle speed can be expressed as follows [14]:…”
Section: Milling Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, the surface profile error can be directly determined by the applied feed rate and axial cut depth during milling operation. By curve fitting on the realistic experiments undertaken beforehand, the current applied to spindle motor with respect to rotational spindle speed can be expressed as follows [14]:…”
Section: Milling Dynamicsmentioning
confidence: 99%
“…The estimated cutting torque, T c , with respect to spindle speed, ω m , and the actual spindle motor current at cutting mode, I, can be described as follows [14]:…”
Section: Milling Dynamicsmentioning
confidence: 99%
“…It is noteworthy that Kim GD and Chu CN, 26 X Li et al, 27 and S Aggarwal et al 28 proposed indirect cutting force measurement by monitoring motor current. This method has good accuracy and can also be used for indirect energy measurement.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of technology for digital servo controllers, intelligent components integrated with internal and external sensors are widely adopted in CNC machine tools. 28,29 The motor current signal and speed controlled by the digital servo can be read out and written by the CNC and PC real time. This is a novel indirect method to measuring and calculating information such as cutting power and input power.…”
Section: Introductionmentioning
confidence: 99%
“…Many other machining physical variables, such as cutting force and tool wear, are related to the feed-motor current. Aggarwal et al [11] identified the cutting torque and tangential cutting force coefficient from the spindle motor current, Jeong and Cho [12] estimated the cutting force from the rotating and stationary feed-motor current, and Rizal et al [3] detected the tool breakage in CNC high-speed milling based on the feed-motor current. Kim and Jeon [13] show that feedmotor is better for the control of the CNC milling process than cutting forces.…”
Section: Introductionmentioning
confidence: 99%